Studi pengaruh erupsi abu vulkanik gunung agung terhadap hasil pengukuran partikel tersuspensi - Rahmat Nugroho; Riza Rizkiah; Agit Setiyoko (Universitas Insan Cendekia Mandiri, 2020)
Mount Agung with an altitude of 3.142 meters above sea level is located in Karangasem. This mountain is one of the active volcanoes in Indonesia. Some dangerous impacts caused by the eruption of Mount Agung are acid rain, earthquakes, lava/lava flow, landslides/mudflow, smoke from lava, pyroclastic, rain of volcanic ash, and rocks and also volcanic gas. One of them which is Rain of volcanic ash can cause blisters on the skin and eyes as well as respiratory irritation. For long-term effects can cause silicosis (lung disease resulting from dust) and chronic lung disease. This study was conducted to determine the Mount Agung volcanic ash eruption effect on the results of SPM concentration measurements at the Jembrana Climatology Station using comparative data and sample data obtained from SPM, VONA concentration measurement data, and the HYSPLIT Volcanic Ash (NOAA) models.